2001
DOI: 10.1291/hypres.24.119
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelin-1/Endothelin Receptor System in Endotoxic Shock Rats.

Abstract: Endothelin (ET)-1, a potent vasoconstrictor peptide derived from the endothelium, is markedly increased in endotoxic shock, although the pathophysiological role of ET-1 under septic conditions remains obscure. To delineate the role of ET-1 and its receptor subtype in endotoxic shock, we here attempted to determine the changes of circulating levels of ET-1 and its biosynthetic intermediate big ET-1 in endotoxic shock rats, to evaluate the gene expression of ET-1 as well as the ET-1 receptor subtypes (ETA and ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
3
22
2
Order By: Relevance
“…Taken together, our previous and current results suggest a role of Gα13 in ETBR-mediated ET-1 autoinduction and other ET-1-mediated pathophysiological reactions. It is well known that endothelin production is up-regulated by various stimuli such as TGF-β, tumor necrosis factor (TNF)-α, interleukins, insulin, norepinephrin, angiotensin II (via AT1 receptors), thrombin, and other physicochemical factors (22,23,27). Since Gα13 interacts with AT1 receptors and thrombin receptors (3,5), Gα13 could play an important role in induction of endothelin by these peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our previous and current results suggest a role of Gα13 in ETBR-mediated ET-1 autoinduction and other ET-1-mediated pathophysiological reactions. It is well known that endothelin production is up-regulated by various stimuli such as TGF-β, tumor necrosis factor (TNF)-α, interleukins, insulin, norepinephrin, angiotensin II (via AT1 receptors), thrombin, and other physicochemical factors (22,23,27). Since Gα13 interacts with AT1 receptors and thrombin receptors (3,5), Gα13 could play an important role in induction of endothelin by these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Gα13 regulates Na/H exchanger activity (7,8), extracellular signal regulated kinase (ERK), c-Jun NH2-terminal kinase (JNK) (9 -11), nuclear factor κB (NF-κB) (12) and the activity of the low molecular weight GTPase, Rho (13 -15), and is also capable of neoplastic transformation, induction of apoptosis, and stimulation of actin reprotein kinases (ERK, JNK, and p38) (23,24). Because of its vasoconstrictor and growth-promoting action, numerous studies indicate that ET-1 is involved in the pathogenesis of a broad spectrum of renal and cardiovascular diseases (21,22,(25)(26)(27). Previous studies have demonstrated that ET-1 induced ET-1 production through ETAR and/or ETBR-mediated pathways, suggesting that a sustained ET-1 autocrine loop contributes to the progression of cardiovascular and renal diseases (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…The femoral vein was cannulated for the administration of salusins, and a saline-filled PE50 polyethylene catheter placed in the femoral artery was connected to a pressure transducer for continuous recordings of blood pressure and heart rate (HR) as described. 6 An electromagnetic flow probe was attached to the abdominal aorta to estimate arterial blood flow (ABF) with an electromagnetic flowmeter (MFV-1100; Nihon Koden). Data were acquired with a polygraph (RM-6000; Nihon Koden).…”
Section: Effects Of the Intravenous Infusion Of Salusins On The Hemodmentioning
confidence: 99%
“…Firststrand cDNA from each mRNA was generated by a reverse transcription method using a First-Strand cDNA Synthesis Kit (Amersham Pharmacia Biotech, Piscataway, USA) (20). Rat and human iNOS mRNA was amplified using synthetic oligomers as probes (rat: forward 5 -GAAGGCTGGAACTA ACTGC-3 , complement 5 -TGCCTTGCTGAATGAACTT G-3 ; human, forward 5 -TACTCCACCAACAATGGCAA-3 , complement 5 -GATGAGCTGAGCATTCCACA-3 ), detected and quantified in real time using a Light Cycler TM (Roche Diagnostics, Basel, Switzerland), as previously described (21,22).…”
Section: Real-time Quantitative Reverse Transcription (Rt)-pcrmentioning
confidence: 99%